TANTANGAN MEMBANGUN MANAJEMEN DAN PENGUKURAN KINERJA SEKTOR PUBLIK DI INDONESIA - M. Rizki Pratama (Universitas Kadiri, 2021)
Management and performance measurement in the public sector are inherently more complex compared to the business sector. Conflicting values such as politics and abstract performance targets make public sector performance management and measurement have distinctive points with different challenges as well. This study aims to describe the various challenges that occur in the context of developing management and performance measurement of the public sector in Indonesia after the implementation of The Law Number 5 of 2014 concerning Civil Servants. The researcher applied a literature study by conducting literature inclusion on two main bases, namely internal and external problems in management and public sector performance measurement. In the end, there are four challenges that must be considered in order to further improve the management and performance measurement of the public sector in Indonesia, namely managing the good and bad impacts of management and performance measurement, managing bias and independence of performance appraisal, managing performance during times of disruption and pandemic and managing the performance of the millennial generation.